Pengaruh profitability, liquidity, growth asset, firm value, dan structure value equity terhadap dividen policy pada perusahaan property & real estate yang terdaftar di bursa efek indonesia periode 2012-2016 - michael tanoto michael (Akuntansi Prima, 2021)
The objective of the study is to test and analyze the effects of liquidity, leverage, company growth, firm value, and profitability on dividend policies in the Property & Real Estate companies on the Indonesia Stock Exchange in the period of 2012-2016. The research was based on information obtained from the Indonesia Stock Exchange. The research used a purposive sampling technique. The research populations were Property & Real Estate companies listed on the Indonesia Stock Exchange in 2012-2016 with the total samples of 15 companies. The research data were analyzed by using multiple linear regression analysis. The result shows that profitability (ROA) has a significant effect on dividend policy on Property & Real Estate companies on the Indonesia Stock Exchange and simultaneously, Liquidity (CR), Leverage (DER), Growth Asset (TA) and firm value do not have any significant effect on dividend policy on Property & Real Estate companies in the Indonesia Stock Exchange